Benefits of implementing the 15-minute city concept in stimulating the potential of social urban resurgence - Agnieszka Michalska-Żyła (Acta Universitatis Lodziensis: Folia Sociologica, 2023)
The issue presented in the article is a proposal to look at a specific vision of the sociospatial organization of the city, namely the concept of the 15-minute city. In this proposed approach, this concept can become a source of inspiration for urban development, as well as a stimulating factor for the social potential of the urban community, which form the basis for the resurgence of cities after the crisis. In the theoretical realm, the basis for the considerations presented in this text is a socio-spatial perspective, according to which the city is perceived as a socio-spatial structure that is reproduced through daily social practices, reflecting both institutionalized patterns and the material organization of space. This text contributes to the discussion about the potential benefits of applying the 15-minute city concept for the development and resurgence of cities in line with the idea of livable cities, ensuring a high quality of life for their residents.